"Mujeres recaudan dinero, vestidos, viveres y medicamentos en ayuda de los españoles". Copied from CNT-collection
"Mujeres recaudan dinero, vestidos, viveres y medicamentos en ayuda de los españoles". Copied from CNT-collection.